A Case Study in the Development of Fibrinolytic Therapy in a Community Hospital in Indonesia - Handrian Purawijaya; Isabella Anjelin (Universitas Malahayati Lampung, 2023)
ABSTRACT Coronary heart disease (CHD) is one of the leading causes of mortality in Indonesia aside from stroke. To reduce the mortality rate, a highly time-dependent, adequate therapy is needed for patients with electrocardiographic features of ST-Elevation Myocardial Infarction (STEMI). The gold standard for reperfusion therapy is thirty minutes for fibrinolytics and ninety minutes for primary PCI. For a community hospital, conducting the reperfusion therapy can be a challenge due to various factors, including human resources, standard operating procedures, and the infrastructure needed. However, to refer the patient to a tertiary hospital often requires time longer than ninety minutes. Therefore, community hospitals should be able to act as the front line of the healthcare system by facilitating fibrinolytic therapy to reduce the mortality rate of CHD in Indonesia. Development of fibrinolytics treatment in community hospitals can be done by creating an expert-reviewed SOP, providing competent human resources, and equipping the hospital with the necessary infrastructure for the service. These are all done in order to keep up with the